2021
DOI: 10.1097/scs.0000000000008273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Auricle Reconstruction Using Tissue Expanders With Skin Grafting and Auricle Reconstruction Using Tissue Expanders Without Skin Grafting: A Single-Arm Meta-Analysis

Abstract: Objective: The authors conducted this meta-analysis to compare the efficacy of auricle reconstruction using tissue expanders with skin grafting and auricle reconstruction using tissue expanders without skin grafting by comparing the 6 major evaluation indicators. Methods: The databases such as PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, Wanfang, and VIP information databases were searched. Results: By comparison, the authors found that, the satisfaction rate, the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Sometimes, negative results are also important for clinical research. A single-arm meta-analysis found that there is no significant difference in the efficacy of the treatment between auricle reconstruction using tissue expanders with skin grafting and auricle reconstruction using tissue expanders without skin grafting 49 . An additional meta-analysis based on 12 clinical studies found no significant differences between the Brent technique and the Nagata technique in terms of infection risk, necrosis, cartilage exposure, hematoma formation, and hypertrophic scarring 50…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes, negative results are also important for clinical research. A single-arm meta-analysis found that there is no significant difference in the efficacy of the treatment between auricle reconstruction using tissue expanders with skin grafting and auricle reconstruction using tissue expanders without skin grafting 49 . An additional meta-analysis based on 12 clinical studies found no significant differences between the Brent technique and the Nagata technique in terms of infection risk, necrosis, cartilage exposure, hematoma formation, and hypertrophic scarring 50…”
Section: Methodsmentioning
confidence: 99%